2018
DOI: 10.7554/elife.36157
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 threonine 11 phosphorylation by Sch9 and CK2 regulates chronological lifespan by controlling the nutritional stress response

Abstract: Upon nutritional stress, the metabolic status of cells is changed by nutrient signaling pathways to ensure survival. Altered metabolism by nutrient signaling pathways has been suggested to influence cellular lifespan. However, it remains unclear how chromatin regulation is involved in this process. Here, we found that histone H3 threonine 11 phosphorylation (H3pT11) functions as a marker for nutritional stress and aging. Sch9 and CK2 kinases cooperatively regulate H3pT11 under stress conditions. Importantly, H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…The Workman group showed that H3T11 was phosphorylated by both Sch9 and Cka1, and reported that Δsch9 and Δcka1 as well as H3T11A prolonged CL 20 . Although this seems opposite to our result where the phosphorylated mimic H3T11D showed CLE, we note that the Δsch9 mutant strain will facilitate activated expression of Msn2/4 stress response genes associated with CLE 40 , and it is not clear if the CLE observed was due to absence of H3T11 phosphorylation or induction of stress response genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Workman group showed that H3T11 was phosphorylated by both Sch9 and Cka1, and reported that Δsch9 and Δcka1 as well as H3T11A prolonged CL 20 . Although this seems opposite to our result where the phosphorylated mimic H3T11D showed CLE, we note that the Δsch9 mutant strain will facilitate activated expression of Msn2/4 stress response genes associated with CLE 40 , and it is not clear if the CLE observed was due to absence of H3T11 phosphorylation or induction of stress response genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although this seems opposite to our result where the phosphorylated mimic H3T11D showed CLE, we note that the Δsch9 mutant strain will facilitate activated expression of Msn2/4 stress response genes associated with CLE 40 , and it is not clear if the CLE observed was due to absence of H3T11 phosphorylation or induction of stress response genes. A phosphorylated mimic H3T11D was not tested 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dietary stresses, especially the best characterized caloric restriction (CR), but also high-fat or low-protein diet result in epigenetic modifications that are conserved across evolution. In S. cerevisiae , nutritional stress leads to increased phosphorylation of histone H3 threonine 11 (H3pT11) by Sch9 and CK2 kinases, a change that is implicated in transcriptional activation and accelerates aging [169]. Accordingly, H3T11A mutants have extended chronological lifespan and increased stress resistance [169].…”
Section: Stress and Epigeneticsmentioning
confidence: 99%
“…In S. cerevisiae , nutritional stress leads to increased phosphorylation of histone H3 threonine 11 (H3pT11) by Sch9 and CK2 kinases, a change that is implicated in transcriptional activation and accelerates aging [169]. Accordingly, H3T11A mutants have extended chronological lifespan and increased stress resistance [169]. Also in yeast, a potential epistatic behavior was established between the loss of histone H4 N-terminal acetylation (caused by deletion of N-alpha-terminal acetyltransferase NAT4 ) and lifespan extension under CR conditions, since nat4 deletion mutants have extended lifespan under normal growth conditions but not under CR [170].…”
Section: Stress and Epigeneticsmentioning
confidence: 99%